Land Use Land Cover and Climate Change impacts on Agroecosystem Services Provisioning in Riverine Areas of Pendjari Reserve in Benin, West Africa - MAKPONSE, DOSSA ARMAND (KNUST, 2024)
Examining the effects of land use and land cover change (LULCC) on biodiversity loss and human wellbeing in the Pendjari Reserve, a biodiversity hotspot in West Africa that has seen human disturbances for years, is the primary goal of this study. The study employed Landsat images and utilized the Random Forest classification software to analyze the dynamics of LULC for 1998, 2007, 2013, and 2020. The expected LULC for 2035 was projected using Terset 18.21. To learn more about household socio- economics characteristics and the advantages of trees in the townships from Tanguieta and Materi, information from 361 farmers was gathered. The influence of farm size, landholding, and district on tree diversity, tree species richness, and tree abundance, were examined as their combined impacts. The study unveiled notable alterations in LULC patterns, such as a reduced wooded savannah and a rise in shrub, cropland, and fallow land. Settlement areas experienced an increase in the studied period. The predicted results indicated an imminent slight decrease in wooded savannah, increase in shrub savannah, cropland, and fallow land, as well as a reduction of settlement areas in the future. Furthermore, farmers' preferences for tree and crop associations were assessed, with Parkia biglobosa identified as the tree species with the largest mean diameter at breast height (dbh) and height. At the same time, Vitellaria paradoxa had the highest height in Materi and Tanguieta. Tree benefits played a crucial role in selecting trees for agroforestry systems, with provisioning services followed by supporting services being the most common ecosystem benefits derived by local communities. Tree-crop associations varied among the farmers. The study examined the effects of tree conservation on agricultural output in agroforestry systems within the same study region as well as the impact of climate trends on critical crop yields. Findings revealed a substantial positive (warming) trend in temperature and a decrease in rainfall. There was a general positive warming trend observed between 1981 to 2020. Results showed that the lowest temperature positively and considerably impacted maize yields, while rainfall and relative humidity adversely affected respectively negatively and positively maize yields. The minimum temperature and relative humidity had a positive and substantial impact on sorghum. The maximum temperature and relative humidity negatively impacted cotton yield, but rainfall had affected positively cotton yields. Maximum and minimum temperature positively and significantly impacted cowpea yields. The Exponential regression model indicated that soil physicochemical characteristics and distance between tree and crop were the primary variables influencing crop yields in agroforestry systems. Furthermore, the study demonstrated that the maximum carbon stored by wooded savannah was projected to be 494,198.1 Mg C ha-1 in 2050, which decreased to 387,059.4 Mg C ha-1 in 2020 and 387,047.2 Mg C ha-1 in 2035. The lowest value of carbon is projected to be sequestered from 2020 to 2035, over a period of fifteen years. The highest gain and loss of projected carbon to sequestered for the period 2020 - 2050 is 108,947 Mg C ha-1 and -57, 996 Mg C ha-1 and the period 2035 -2050 is 108878 Mg C ha-1 and -57984.6 Mg C ha-1, respectively. Conversely, the lowest gain and loss were anticipated from 2020 to 2035, with value of 845.56 Mg ha-1 and -47.52 Mg C ha-1, respectively.